2012
DOI: 10.1016/j.worlddev.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization, Inequality, and Poverty in Brazilian States

Abstract: This paper studies the impact of trade liberalization and international trade on household income inequality and poverty using detailed micro-data across Brazilian states, from 1987 to 2005. Results suggest that Brazilian states that were more exposed to tariff cuts experienced smaller reductions in household poverty and inequality. If significance of results on Brazilian states depends on the choice of poverty and inequality indicators, robust and contrasting results emerge when we disaggregate into rural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 25 publications
3
82
1
2
Order By: Relevance
“…Moreover, in earlier related work, Topalova (2007) finds, albeit in somewhat less technically secure estimates, that whereas import exposure increases poverty, export exposure over this period reduces it. Castilho et al (2012) find a similar dichotomy between exportand import-oriented results in Brazil. For all their elegance, Topalova's (2010) estimates do not take us much closer to answering the question of whether liberalization helped to reduce Indian poverty.…”
Section: Households and Marketssupporting
confidence: 55%
“…Moreover, in earlier related work, Topalova (2007) finds, albeit in somewhat less technically secure estimates, that whereas import exposure increases poverty, export exposure over this period reduces it. Castilho et al (2012) find a similar dichotomy between exportand import-oriented results in Brazil. For all their elegance, Topalova's (2010) estimates do not take us much closer to answering the question of whether liberalization helped to reduce Indian poverty.…”
Section: Households and Marketssupporting
confidence: 55%
“…As a result, some researchers have focused on the interaction among trade openness, inequality and poverty. Some empirical studies revealed that trade openness has influenced income inequality or poverty negatively (Bucciferro, 2010;Castilho et al, 2012), while other studies revealed that trade openness affected income inequality or poverty positively (Khan and Bashir, 2013;Wahiba, 2013;Székely and Samano, 2012). Furthermore, relatively few studies have reached a conclusion that there has been no statistical relationship among trade openness, income inequality and poverty (Khan and Bashir, 2013;Trabelsi and Liouane, 2013).…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…However, some studies did not find any significant relationship between trade and income inequality (Edwards, 1997;Li et al, 1998;Vivarelli, 2004). Castilho et al (2012) studied trade liberalization, poverty and inequality issues in Brazilian states and they came to a conclusion that trade liberalization increases the poverty and inequality in urban areas while it may reduce the inequality in the countryside. Perera et al (2014) identified the little bit different result that income inequality and poverty both fall in urban, rural, and estate sectors in Sri Lanka due to trade openness.…”
Section: Trade Openness and Inequalitymentioning
confidence: 99%